The Tensions Between EFL Teacher Identities and INSET in the Turkish Context - Fatih Güngör (Universidad Nacional de Colombia, 2017)
Due to the insufficiency of current in-service training courses which are far from the collaboration and the reflection of teachers, the current study scrutinizes the incongruities between teacher identities and in-service training programs offered by the Ministry of National Education in Turkey based upon the use of the activity theory. In this narrative study, two English as a foreign language teachers reflected on their environment, behaviors, beliefs, competencies, and missions under the heading of teacher identity concept. The results suggest that teachers need a supportive community of practice and a well-tailored mentoring system to be able to reflect on themselves and the context in which they are teaching.